Simultaneous growth of several bicrystals oriented by common single-crystal seed - Kazarov, Yu.G. (Functional Materials, 2015)
The hetero-homoepitaxy phenomenon is shown efficient for simultaneous growth of five Zn-bicrystals identically oriented by one single-crystal seed. The crystallographic, geometrical and thermal requisites to achieve the successful growth and specify the grain boundary orientation identical for all bicrystals are analyzed for closely packed pure metals.